[quotation] On poverty - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On poverty: 'If women can defeat poverty through hard work to increase their income levels, why not others, not to mention men who are gifted with natural strength to till the land and other physical jobs to earn income?' Rebecca Fonkem, Rural Women...